Effects of detraining on breathing pattern and ventilatory efficiency in young soccer players - Alvero-Cruz, J. R.; Ronconi, M.; Garcia Romero, J.; Naranjo Orellana, J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: This study investigated the effects of detraining on breathing pattern. The aim of this study was to evaluate the effect of a six-week detraining period on breathing patterns and ventilatory efficiency. METHODS: Fourteen young soccer players were evaluated at the end of a competitive season and after a six-week detraining period. Assessment of respiratory efficiency was based on VE/VCO2 slope changes below 70% of exercise intensity. All participants underwent twice an incremental graded exercise test up to exhaustion. RESULTS: No differences in breathing frequency and inspiratory time/total time ratio (Ti/Ttot) were found after detraining (P>0.05). Differences in tidal volume (VT), VT/Ti quotient and VE were significant (P<0.05) at between 40 to 100% of exercise intensity. The VE/VCO2 slope did not change (P>0.05) during a postdetraining maximal incremental test. CONCLUSIONS: A six-week detraining period causes changes in inspiratory flow but does not affect the inspiratory time/total respiratory cycle time ratio. The overall ventilatory efficiency of the respiratory system remains constant and is not affected by detraining.